Influence of carotid atherosclerotic plaques on pulse wave assessment with arterial tonometry. Issue 8 (August 2017) - Grillo, Andrea; Simon, Giulia; Salvi, Paolo; Rovina, Matteo; Baldi, Corrado; Prearo, Ilaria; Bernardi, Stella; Fabris, Bruno; Faini, Andrea; Parati, Gianfranco; Bardelli, Moreno; Carretta, Renzo
Abstract : Objective: Aortic stiffness and central pressure measurements have become increasingly important for the overall estimation of cardiovascular risk. The aim of this study is to verify whether the presence of stenosis in the carotid arteries due to atherosclerotic plaques may induce a bias in the measurement of carotid–femoral pulse wave velocity (PWV) and in the analysis of central pulse waveform variables assessed by carotid tonometry. Methods: Eighty-four patients (age: 67.1 ± 12.4 years) undergoing screening for carotid atherosclerosis were enrolled, divided into three groups according to carotid ultrasound findings (NASCET criteria): 28 patients without significant stenosis, 30 patients with bilateral plaques, and 26 patients with right or left monolateral stenosis. PWV and other variables derived from the central pulse waveform analysis (central blood pressure, augmentation index and forward and backward waves) were measured at both right and left carotid arteries by a validated PulsePen tonometer. A repeatability study was performed in 28 young healthy patients (age: 25.4 ± 2.9 years). Results: A high degree of correlation was found between bilateral measurements in all groups, and particularly in groups with monolateral carotid stenosis, with no significant difference attributable to lateralized stenosis. Right–left differences in asymmetric groups were 0.35 ± 5.12 mmHg ( R 2  = 0.960) for central blood pressure, −2.12 ± 7.39% ( R 2  = 0.743) for augmentation index, 0.64 ± 1.56 m/s ( R 2  = 0.947) for PWV, 0.08 ± 8.48 mmHg for forward wave ( R 2  = 0.742) and 0.35 ± 2.35 mmHg for backward wave ( R 2  = 0.907). Conclusion: Measurement of PWV and of variables derived from the central pulse waveform analysis by carotid tonometry is not biased by the presence of local atherosclerotic plaques. Abstract : Supplemental Digital Content is available in the text